Crystallographic and SAR analyses reveal the high requirements needed to selectively and potently inhibit SIRT2 deacetylase and decanoylase. Issue 1 (8th January 2019) - Yang, Ling-Ling; Xu, Wei; Yan, Jie; Su, Hui-Lin; Yuan, Chen; Li, Chao; Zhang, Xing; Yu, Zhu-Jun; Yan, Yu-Hang; Yu, Yamei; Chen, Qiang; Wang, Zhouyu; et al.
Abstract : A high-quality X-ray crystal structure reveals the mechanism of compound1a inhibiting SIRT2 deacetylase and decanoylase. Abstract : A high-quality X-ray crystal structure reveals the mechanism of compound1a inhibiting SIRT2 deacetylase and decanoylase. Structure–activity relationship (SAR) analysis of the synthesized derivatives of1a reveals the high requirements needed for selective inhibitors to bind with the induced hydrophobic pocket and potently inhibit sirtuin 2 deacetylase.